Future Role of Bio-Microorganism Pesticide in Pakistan - Sumia Urainab (Food, Agriculture and Natural Resources - NETWORKS, 2022)
Microbial pathogens are disease-causing organisms that are spread in vast quantities in the pest population, similar to how chemical pesticides are applied. These microorganisms are utilized through introduction or inundative applications for organic control of bug bothers. Insects are vulnerable to a variety of illnesses brought about by infections, microscopic organisms, the parasite, protozoa, and nematodes, among different microorganisms. Insect microbial pathogens are being studied in depth in order to develop environmentally acceptable pest management solutions for agriculture. These days, plant protection environments and insect pest control are hampered by the development of chemical resistance and residues at higher trophic levels. Bio-pesticides have been replacing chemical pesticides to protect nontarget creatures from the harmful effects of chemicals in recent years. This research discusses the insecticidal characteristics of microorganisms, just as their potential utility in bother the board.